Pengaruh Kondisi Operasi Terhadap Kualitas Aluminium Stearat dalam Reaktor Batch - Suminar, Dian Ratna; Lingga Permana, Rezza; Amellia, Yashinta; Ghozali, Mukhtar; Sudarman, Robby; Sihombing, Rony Pasonang (Jurnal Teknik Kimia USU, 2026)
Aluminum stearate has the same potential as aluminum soap as a lubricant additive that can be developed towards standardization of commercial products. The research stages consist of: (1) Making sodium soap through saponification reaction (stearic acid and NaOH), (2) Replacing sodium metal with aluminum metal through trans-saponification reaction, (3) Purifying the product by washing with distilled water, (4) Separation and drying of the product using a Buchner funnel and oven at 100 oC for 3 hours, (5) Analytical test of aluminum stearate product: testing melting point, water content, ash content, free fatty acid content, quantitative content using AAS spectrophotometer, and solubility test. The results of the study showed that aluminum stearate can be made through 2 reaction stages, namely saponification and trans-saponification in the form of a white powder with a melting point of 115.7 oC, ash content of 13.93%, maximum free fatty acid content of 0.9372%, and insoluble in water and chloroform; partially soluble in n-hexane and toluene waste; and soluble in paraffin, methanol, and nitric acid.